Si nano-cavity enabled surface-enhanced Raman scattering signal amplification. (2nd September 2019) - Chen, Jian; Tang, Peng; Liu, Guiqiang; Yi, Zao; Liu, Xiaoshan; Pan, Pingping; Liu, Zheng-qi
Abstract: Surface-enhanced Raman scattering (SERS) detection technique has gained much attention as a powerful analytical tool in recent years. Nevertheless, the attention was mainly focused on the efficient scattering platform by structuring metals themselves, leading to more complex platforms and higher costs. Herein, a new and simple strategy to prepare large-area, low-cost, high-performance SERS substrate is introduced. Ultra-thin semiconductor silicon (Si) film is used as the functional layer for the metallic nano-particles based meta-surface. During the SERS sensing process, the emergence of a Si layer is observed to provide three key contributions: (1) to produce a maximal enhancement factor (EF) ∼470% compared to that of the bare meta-surface, (2) to keep a higher spectral stability for the Raman signal, and (3) to physically interdict the contact between the metal and the molecule. Moreover, the Si film's thickness is down to the scale of an electron's Bohr radius, indicating efficient electronic oscillations for the semiconductor material under electromagnetic excitation. The charge transfer behaviors between the molecules and the Si layer and metal nano-particles can also emerge. These findings could pave new insights on the surface-enhanced spectroscopy and lead to applications for the high-performance, large-area, low-cost SERS sensing process.